2005
DOI: 10.1007/s10067-005-1127-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings in a case of remitting seronegative symmetrical synovitis with pitting edema

Abstract: We describe a case of remitting seronegative symmetrical synovitis with pitting edema (RS3PE syndrome) in a 66-year-old man. This report discusses magnetic resonance imaging findings of RS3PE syndrome and the changes after steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…We have investigated this hypothesis more intensely in the present case by serologic variables and radiographic methods. These abnormalities have been reported previously [3][4][5][6][7][8][9]; however, this is a first report of a patient showing recovery of all these parameters at once after treatment. In vitro studies have revealed that IL-6 induces the production of VEGF [10], MMP-3 [11], and SAA [12].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We have investigated this hypothesis more intensely in the present case by serologic variables and radiographic methods. These abnormalities have been reported previously [3][4][5][6][7][8][9]; however, this is a first report of a patient showing recovery of all these parameters at once after treatment. In vitro studies have revealed that IL-6 induces the production of VEGF [10], MMP-3 [11], and SAA [12].…”
Section: Discussionsupporting
confidence: 72%
“…We previously reported that the serum level of vascular endothelial growth factor (VEGF) was markedly elevated in patients with RS 3 PE syndrome [3]. As diagnostic imaging tools, magnetic resonance imaging (MRI), ultrasonography (USG), and Gallium (Ga)-67 scintigraphy are useful for the detection of inflammatory sites [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…6 Besides, magnetic resonance imaging revealed symmetrical subcutaneous edema and tenosynovitis in flexor tendon sheath. 7 After steroid therapy, edema and tenosynovitis might resolve completely. 7 Among these patients, 59% of them had HLA-B27 positivity in contrast to 24% in the general population, 8 but no causal relationship can be established yet.…”
Section: Discussionmentioning
confidence: 99%
“…7 After steroid therapy, edema and tenosynovitis might resolve completely. 7 Among these patients, 59% of them had HLA-B27 positivity in contrast to 24% in the general population, 8 but no causal relationship can be established yet. Moreover, biopsy proved that autoimmune hepatitis had been reported to be related to RS3PE syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, Magnetic resonance imaging (MRI) has been reported to be a sensitive diagnostic measure of evaluation of predominant involvement of the extensor tendons in RS3PE, showing symmetrical subcutaneous edema and increased vascularity of the synovium as well as contrast enhancement of the synovial proliferation. 7,8 MRI is also useful for monitoring the disease activity in RS3PE syndrome. On the other hand, Agarwal V et al proposed ultrasonography as another diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%